The demon's den - Dixon, Franklin W. (Dixon, Franklin W. Hardy boys mystery stories., 1984)
The Hardy boys, vacationing in Vermont, offer to help the police locate a missing camper and find themselves involved with a doomsday cult, a deadly strain of bacteria, and possibly the devil.